The Impact of the Provincial Minimum Wage (UMP) Policy on the Income of Formal Sector Workers in DKI Jakarta - Muh Hylmi Adhitya Nindra; Zahran Yaka Resyawal; Eva Hany Fanida; Melda Hidayat (Pustaka Digital Indonesia, 2026)
This study aims to determine the impact of variables on minimum wage income in the DKI Jakarta Province area. Changes to regulations such as Government Regulation No. 51 of 2023 aim to balance worker protection and business sustainability, as well as include workers' economic contributions and decent living standards in the wage formula. This research is a policy effort to systematically improve the minimum wage determination structure in Indonesia, including DKI Jakarta Province. However, the fact is that although the regulation is intended to provide a more systematic framework for calculating and increasing the minimum wage, it is not yet fully effective in guaranteeing an increase in the minimum wage for workers. The regulation should focus on more efficient and transparent policies so that wage policymakers are fairer, more adaptive and sustainable for workers. This research uses a descriptive research method with a quantitative approach from various official documents, reports, journal articles, as well as references related to minimum wage policies and community income. This research shows that the minimum wage income in the city of Jakarta is very influential, especially for the underprivileged. Therefore, to reduce the impact of the minimum wage policy, a policy is needed which can help reduce income in the city of Jakarta.